Synthesis of a new porous geopolymer from foundry dust to remove Pb2+ and Ni2+ from aqueous solutions. (15th May 2022) - Ma, Xianyao; Xu, Defu; Li, Yingxue; Ou, Zuochen; Howard, Alan
Abstract: This study reports the development of a new geopolymer from foundry dust (FD) and its use as a Pb 2+ and Ni 2+ adsorbent in aquatic solutions. FD is a solid waste produced in huge quantities by the foundry industry which without careful management and recycling can seriously pollute the environment. Research on the resource utilization of FD is very lacking, and there is no research on the adsorption of heavy metals using geopolymers synthesized by FD. In this study, FD was combined with water glass and NaOH as alkali activators and oleic acid to synthesize a foundry dust-based geopolymer (FDG). Addition of hydrogen peroxide (H2 O2 ) improved pore structure and increased the specific surface area of FDG from 31.83 m 2 /g to 61.11 m 2 /g, thereby increasing FDG adsorption capacity of Pb 2+ (251.56 mg/g) and Ni 2+ (60.16 mg/g), and shortening the equilibrium time to 2 h. However, the adsorption capacity of FDG for Ni 2+ was inhibited by Pb 2+ where the two ions coexist in solution. The adsorption process was well fitted to the Langmuir model and the pseudo-second-order kinetic model, indicating that the adsorption mechanism is mainly chemical adsorption including electrostatic attraction and ion exchange. Results show that foundry dust-based geopolymer has excellent Pb 2+ and Ni 2+ adsorption properties and it provides a new way for the resource utilization of foundry dust.